(untitled) (Bangladesh Journal of Agriculture, 2024)
The physico-chemical characteristics of five distinct soybean cultivars that were gathered from diverse sources from April to October 2020 were examined in this study. The experiment was conducted in a Completely Randomized Design (CRD) with three replications. Seed weight, moisture percentage, ash percentage, oil percentage, protein percentage, chemical constants (saponification, acid, and iodine value), fatty acid composition, and mineral composition of the seeds of five soybean genotypes and their cakes were estimated. BINA Soybean-3 had the highest seed weight (159.01g) among the five varieties. The moisture level of the beans ranged from 9.06% (BARI Soybean-6) to 9.84% (BINA Soybean-3). The variety, Shohag, had the highest concentration of ash (5.20%). The oil content ranged from 14.88% in BINA Soybean-3 to 16.87% in BU Soybean-2. The maximum amount of oil cake was found in BU Soybean-2 (83.23%). The percentage of protein ranged from 38.01% (BINA Soybean-5) to 52.20% (BU Soybean-2). BINA Soybean-3 has the highest iodine number (79.65) while BU Soybean-2 has the highest saponification value (189.85), and BINA Soybean-3 has the lowest acid value (0.90). The largest amounts of linoleic acid (54.39%), linolenic acid (9.56%) and palmitoleic acid (0.18%) were found in BU Soybean-2. The variety Shohag had the highest levels of phosphorus (0.84%), copper (29.24 ppm), calcium (0.23%), iron (86.75ppm), and sulphur (0.09%) in terms of mineral compositions. This study found that Shohag had remarkable mineral compositions, while BU Soybean-2 outperformed the other soybean varieties in terms of quality. Bangladesh J. Agri. 2024, 49(1): 106-116